2005
DOI: 10.1111/j.1741-3737.2005.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

High Hopes but Even Higher Expectations: The Retreat From Marriage Among Low‐Income Couples

Abstract: This study examines why low‐income, unmarried parents who say that they plan to marry at the time their child is born do not follow through on their plans. We use data from a nationally representative birth cohort survey—the Fragile Families and Child Wellbeing Study (N =3,710)—combined with data from an embedded qualitative study—Time, Love, Cash, Caring, and Children (n =47)—to explore the reasons behind this apparent discrepancy. We find that some of the difference between parents’ expectations and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
465
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(501 citation statements)
references
References 26 publications
23
465
2
3
Order By: Relevance
“…With high expectations for work, romantic, and family life, the fixed costs of marriage may now be perceived to be higher among collegeeducated women, and consequently, the liquidity constraints imposed by student loan debt may be a greater deterrent to marriage for women than for men. There is mounting evidence from studies of low-income women that feeling economically stable is a necessary pre-requisite for marriage (Gibson-Davis, Edin, and McLanahan 2005;Joshi, Quane, and Cherlin 2009). This "economic stability" perspective anticipates that higher levels of debt will be most salient in young women's decisions to marry.…”
Section: Potential Differences By Gendermentioning
confidence: 99%
“…With high expectations for work, romantic, and family life, the fixed costs of marriage may now be perceived to be higher among collegeeducated women, and consequently, the liquidity constraints imposed by student loan debt may be a greater deterrent to marriage for women than for men. There is mounting evidence from studies of low-income women that feeling economically stable is a necessary pre-requisite for marriage (Gibson-Davis, Edin, and McLanahan 2005;Joshi, Quane, and Cherlin 2009). This "economic stability" perspective anticipates that higher levels of debt will be most salient in young women's decisions to marry.…”
Section: Potential Differences By Gendermentioning
confidence: 99%
“…Economic uncertainty especially influences those with less education and couples from the lower social strata (PerelliHarris et al 2010). For women with less education, motherhood may be a choice to reduce uncertainty and give structure to their lives (Friedman, Hechter, and Kanazawa 1994;Graham and McDermott 2006), whereas their male partners might not have the financial means to provide for mother and child and to turn the relationship into marriage (Gibson-Davis, Edin, and McLanahan 2005;Kravdal 1999;Mills and Blossfeld 2003;Oppenheimer 2003;Oppenheimer, Kalmijn, and Lim 1997;Sobotka and Toulemon 2008;Perelli-Harris et al 2010). Hence, those facing economic uncertainty may be more likely to cohabit and less likely to marry.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, uncertainty about a man's employment prospects is more tolerable in the context of cohabitation, since cohabitation is often seen as a trial stage before marriage, and the costs of breaking up a cohabiting union are lower than the costs associated with divorce (Ermisch and Francesconi 2000;Oppenheimer 2003). Empirical studies have indicated that a man's ability to fulfil the role of provider remains an important prerequisite for marriage in the United States (Gibson-Davis et al 2005;Sassler et al 2014), as well as in European countries with relatively high levels of gender egalitarianism, such as Norway and Sweden (Wiik et al 2010). Provided the public benefits available to lone mothers (and/or the father's contributions) are sufficient, a woman might view childbearing outside of marriage as preferential to remaining single and childless (Ermisch 2008).…”
Section: Background: the Social Context Of Non-marital Childbearingmentioning
confidence: 99%